2021
DOI: 10.1111/imj.14923
|View full text |Cite
|
Sign up to set email alerts
|

Medical emergency team training: needs assessment, feedback and learning objectives

Abstract: Background There are no published studies assessing learning needs and attitudes prior to attending a medical emergency team (MET) education programme. Aims To conduct a learning needs assessment of MET education programme participants to assess what technical and non‐technical skills should be incorporated. Methods All participants in a MET education programme over a 12‐month period were invited to complete a self‐administered electronic survey. Participants were ICU team members (intensive care registrars an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[ 20 ] As a basic treatment model for modern diseases, MDT is conducive to the development of a multidisciplinary mindset, and trainees can integrate theoretical medical knowledge and clinical specialty practice by participating in the treatment process of emergency trauma patients. [ 21 , 22 ] In our teaching study, we found that both groups of trainees had significantly improved their assessment scores after participating in the MDT model of emergency trauma teaching, suggesting that this method is practical and feasible to be applied to the training teaching. The trainees in the observation group introduced PBL teaching on the basis of MDT through discovering, analyzing, and solving problems in typical cases, which prompted standardized clinical residents to deepen their understanding of theoretical knowledge in teaching practice.…”
Section: Discussionmentioning
confidence: 76%
“…[ 20 ] As a basic treatment model for modern diseases, MDT is conducive to the development of a multidisciplinary mindset, and trainees can integrate theoretical medical knowledge and clinical specialty practice by participating in the treatment process of emergency trauma patients. [ 21 , 22 ] In our teaching study, we found that both groups of trainees had significantly improved their assessment scores after participating in the MDT model of emergency trauma teaching, suggesting that this method is practical and feasible to be applied to the training teaching. The trainees in the observation group introduced PBL teaching on the basis of MDT through discovering, analyzing, and solving problems in typical cases, which prompted standardized clinical residents to deepen their understanding of theoretical knowledge in teaching practice.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, advancing MET, members' knowledge, technical and non‐technical skills, and leadership skills have been emphasized in a current MET's recommendation for improving MET performance 24 . According to recent studies, the educational needs of ICU nurses working in the MET include learning clinical deterioration theory and skills, MET's governance, and non‐technical skills such as task management, communication, professionalism, and teamwork 25,26 . We recommend hospital managers and educators to focus more on the training and education received by MET members, especially those to improve teamwork within the MET.…”
Section: Discussionmentioning
confidence: 99%
“…7 Person analysis, the exploration of specific learner goals by means of interviews or surveys, is well reported in the literature. [1][2][3][4] Less described are the methods of objective task analysis and organizational analysis, which could include direct observation of clinical work or the review of institutional data surrounding patient safety events and quality improvement activities. 8 The intensive care unit (ICU) offers a unique environment where emergency events are frequent, high-stakes, and carefully documented, which makes it an ideal setting to research the specific technical skills, which are deployed during such events.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…Expert recommendations expand needs analysis into 3 main components: organizational analysis, task analysis, and person analysis 7 . Person analysis, the exploration of specific learner goals by means of interviews or surveys, is well reported in the literature 1–4 . Less described are the methods of objective task analysis and organizational analysis, which could include direct observation of clinical work or the review of institutional data surrounding patient safety events and quality improvement activities 8 …”
Section: Introduction and Aimsmentioning
confidence: 99%
See 1 more Smart Citation